PENGARUH PUPUK ORGANIK DAN VARIASI PEMBERIAN AIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAYAM HIJAU (Amaranthus hybridus) - Dewangga, Panji; Widata, Sri; Arnanto, Driska (JURNAL ILMIAH AGROUST, 2025)
This study aims to determine the effect of organic fertilizer on green spinach (amaranthus hybridus) plants, to determine the effect of variations in water supply on green spinach (amaranthus hybridus) plants, to determine the effect of the interaction of organic fertilizer and variations in water supply on the growth and yield of green spinach plants. The location of this research was carried out at the Gemah Ripah Farmer Group, Bausasran, Danurejan District, Yogyakarta City, Special Region of Yogyakarta. With an average rainfall of 2,012 mm/year with 119 rainy days, an average temperature of 27.2°C and an average humidity of 24.7%, and an average altitude of 114 m above sea level. The research was conducted using a Randomized Block Design (RAK) with 2 factors. The first factor is the type of fertilizer (A) with 3 levels. The second factor is the provision of water (B) with 3 levels. Data were analyzed using analysis of variance at the 5% level followed by using Duncan's Multiple Range Test (DMRT) at the 5% level. The variables observed included Plant Height, Number of Leaves, Stem Diameter, Leaf Length, Chlorophyll Content, Fresh Weight, and Dry Weight. The results showed no interaction between the type of organic fertilizer and water provision on Plant Height, Number of Leaves, Stem Diameter, Leaf Length, Chlorophyll Content, Fresh Weight, and Dry Weight.